Formulation and Evaluation of Nanoemulsion of the Phenolic Content of Foeniculum vulgare for Antidepressant and Antihypertensive Potentiality - Das, Sanjita; Rani, Sweta (Indian Journal of Pharmaceutical Education and Research, 2023)
Objectives: Foeniculum vulgare (common name: fennel; family: Umbelifereae) is a well-documented plant with various medicinal properties to manage different types of disease. Depression and hypertension are associated with each other. The study focuses mainly on the evaluation of the antidepressant and antihypertensive effect of the nanoemulsion formulations of the phenolic content of the arial part of Foeniculum vulgare. Materials and Methods: The nanoemulsion formulation (1% and 2% W/V) formulation was formulated and subjected to in vivo screening of its antidepressant activity following forced swim and tail suspension tests in mice, while its antihypertensive effect using salt induces hypertension in wistar rats with BIOPAC power lab. Results: The study measured a significant (p less than 0.01) reduction by Nanoemulsion of Foeniculum vulgare (NFV) in immobility times in mice, which was well comparable to imipramine (15 mg/kg) and so significant (p less than 0.01) normalization of increased blood pressure. It was further interpreted significant (p less than 0.01) increase in the brain level of dopamine and serotonin exhibiting major mechanism behind the antidepressant and antihypertensive potentiality of Foeniculum vulgare. Conclusion: The study suggested the implementation of the use of NFV in the overall treatment of hypertension associated with depression and vice versa.
Keywords: Nanoemulsion; Essential oil; Foeniculum vulgare; Monoamine; Dopamine; Serotonin